(untitled) (Pedagogy of Higher and Secondary Education, 2014)
Bakum Z. P., Lapina V. O. Stages of implementation of educational dialogue into the process of learning foreign languages by future miners. The article describes the stages of introduction an educational dialogue into the process of learning foreign languages as means of forming speech competence of technical specialties students (future miners’ competence); researches specifics of four levels of educational dialogue (basic, intermediate,upper-intermediate and advanced); contains practical recommendations, which will help to avoid mistakes in dialogic learning organization.